Looking beyond returns in selecting a unit trust. - Chiam, Kenneth Siang Roung. (2008)
This study aims to look beyond returns in selecting a unit trust by identifying key information that are currently available and are beneficial to unit trusts investors including turnover ratio, investment objective and style, fund size, expense ratios and other expenses incurred by the investor.